Understanding cultural diversity in the early years - Baldock, Peter. (Sage, 2010)
Taking the discussion about cultural diversity beyond the usual topics of anti-racism & inclusion but without overlooking these issues, this book considers current debates around the alleged failure of multiculturalism, & encourages practitioners to use their own cultural backgrounds & experiences as a way of developing their teaching.